A Spinal Triage Programme Delivered by Physiotherapists in Collaboration with Orthopaedic Surgeons - Bath, Brenna (University of Toronto Press Incorporated, 2012)
Purpose: To describe the characteristics of participants in a physiotherapist spinal triage programme, compare the profiles of patients for whom surgery was and was not recommended by a surgeon, and determine the surgical yield among those referred to surgeons. Methods: Data were collected retrospectively by reviewing charts of people who used the service over a 3-year period (2003–2006). Data from up to1,096 people were used in the analysis; complete data were available for 299 people. Descriptive statistics were used to summarize demographics, clinical features, and management recommendations. Characteristics of those who were and were not recommended for surgery were examined using Pearson's chi-square or Fisher's Exact tests. Results: The majority of 746 participants were classified as “mechanical spine” (92.5%), 2.9% were “other body part,” 2.5% were “medical/other,” and only 2% were classified as “surgical spine.” Recommendations for surgery (by a surgeon) were independent of patients' age, sex, duration of symptoms, residence (urban/rural), source of health care funding, and diagnosis. The surgical yield was 80%. Conclusions: Most people were not considered candidates for surgery. Triage assessment by physiotherapists can increase the efficiency of an orthopaedic surgeon's caseload by reducing the number of non-surgical referrals and can thus help to ensure more timely access to appropriate health care.